Artemisia argyi extract induces apoptosis in human gemcitabine-resistant lung cancer cells via the PI3K/MAPK signaling pathway. (5th December 2022) - Su, San-Hua; Sundhar, Navaneethan; Kuo, Wei-Wen; Lai, Shang-Chih; Kuo, Chia-Hua; Ho, Tsung-Jung; Lin, Pi-Yu; Lin, Shinn-Zong; Shih, Cheng Yen; Lin, Yu-Jung; Huang, Chih-Yang
Abstract: Ethnopharmacological relevance: Artemisia argyi H. Lév. & Vaniot (Asteraceae), also called "Chinese mugwort", is frequently used as a herbal medicine in China, Japan, Korea, and eastern parts of Russia. It is known as "ai ye" in China and "Gaiyou" in Japan. In ancient China, the buds and leaves of A. argyi were commonly consumed before and after Tomb-sweeping Day. It is used to treat malaria, hepatitis, cancer, inflammatory diseases, asthma, irregular menstrual cycle, sinusitis, and pathologic conditions of the kidney and liver. Although A. argyi extract (AAE) has shown anti-tumor activity against various cancers, the therapeutic effect and molecular mechanism of AAE remains to be further studied in lung cancer. Aim of the study: This study aimed to demonstrate the anti-tumor effect of AAE and its associated biological mechanisms in CL1-0 parent and gemcitabine-resistant (CL1-0-GR) lung cancer cells. Experimental procedure: Human lung cancer cells CL1-0 and CL1-0-GR cells were treated with AAE. Cell viability was assessed using the MTT, colony, and spheroid formation assays. Migration, invasion, and immunofluorescence staining were used to determine the extent of epithelial– mesenchymal transition (EMT). JC-1 and MitoSOX fluorescent assays were performed to investigate the effect of AAE on mitochondria. Apoptosis was detected using the TUNEL assay and flow cytometry with Annexin V staining. Result: We found that A. argyi significantly decreased cell viability and induced apoptosis, accompanied by mitochondrial membrane depolarization and increased ROS levels in both parent cells (CL1-0) and gemcitabine-resistant lung cancer cells (CL1-0-GR). AAE-induced apoptosis is regulated via the PI3K/AKT and MAPK signaling pathways. It also prevents CL1-0 and CL1-0-GR cancer cell invasion, migration, EMT, colony formation, and spheroid formation. In addition, AAE acts cooperative with commercial chemotherapy drugs to enhance tumor spheroid shrinkage. Conclusion: Our study provides the first evidence that A. argyi treatment suppresses both parent and gemcitabine-resistant lung cancer cells by inducing ROS, mitochondrial membrane depolarization, and apoptosis, and reducing EMT. Our finding provides insights into the anti-cancer activity of A. argyi and suggests that A. argyi may serve as a chemotherapy adjuvant that potentiates the efficacy of chemotherapeutic agents. Graphical abstract: Image 1